1982
DOI: 10.1210/endo-110-2-398
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulinotropic Action of Cholecystokinin and Caerulein in the Isolated Perfused Rat Pancreas

Abstract: The effect of pure natural porcine cholecystokinin (CCK) and synthetic caerulein on endocrine and exocrine pancreatic secretion was investigated in the isolated perfused rat pancreas in the presence of physiological concentrations of glucose. CCK (0.25 mU/ml) or caerulein (0.01 ng/ml) potentiated the insulin secretion induced by 5.6 mM glucose; a significant increase in pancreatic exocrine secretion was also observed at these doses of CCK or caerulein. Further increases in the concentration of CCK (0.25 to 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Increase in release from the NIL is a distinct possibility, at least for cholecystokinin, which is coreleased with vasopres sin [12] and fordynorphin, which is altered in content in the same way as vasopressin [35], because hyperosmolality in diabetes will un doubtedly lead to an increase in vasopressin release [33], If there is indeed an increase in the release of dynorphin and cholecystokinin from the NIL, the increased secretion of these neuropeptides and P-endorphin may stimu late insulin secretion from the 'residual' pan creatic islets in streptozotocin-treated rats, as a compensatory mechanism for the decrease in insulin secretion. Opioid peptides [36] and cholecystokinin [37] have been shown to be insulinotropic when administered peripher ally. The increase in p-endorphin release from the pituitary could be the result of increased adrenergic stimulation [38],…”
Section: Discussionmentioning
confidence: 99%
“…Increase in release from the NIL is a distinct possibility, at least for cholecystokinin, which is coreleased with vasopres sin [12] and fordynorphin, which is altered in content in the same way as vasopressin [35], because hyperosmolality in diabetes will un doubtedly lead to an increase in vasopressin release [33], If there is indeed an increase in the release of dynorphin and cholecystokinin from the NIL, the increased secretion of these neuropeptides and P-endorphin may stimu late insulin secretion from the 'residual' pan creatic islets in streptozotocin-treated rats, as a compensatory mechanism for the decrease in insulin secretion. Opioid peptides [36] and cholecystokinin [37] have been shown to be insulinotropic when administered peripher ally. The increase in p-endorphin release from the pituitary could be the result of increased adrenergic stimulation [38],…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies, Otsuki's group further demonstrated that CCK-and cerulein-induced insulin secretion is dependent on the glucose concentration ( Fig. 4) (20). Otsuki et al (19)(20)(21)(22) published a number of articles describing this perfusion system.…”
Section: Discussionmentioning
confidence: 98%
“…Previous in vitro studies in rats using natural porcine CCK [2. 13] or cerulein [8,13,14], and in vivo experiments using natural porcine CCK [15] have shown that the insulinotropic effect of CCK is glu cose dependent. This is confirmed in the present study in that even the highest levels of CCK-8 had no effect on insulin release at a perfusate glucose concentration of 2.8 mM ( fig.…”
Section: Discussionmentioning
confidence: 99%